Evaluation and comparison of surface macrotexture and friction measurement methods - Sezen, Halil; Fisco, Nicholas (Journal of Civil Engineering and Management, 2013)
Two- and three-dimensional macrotexture characteristics of various surfaces were measured using five different testing methods including sand patch method, laser profiler, laser texture scanner, circular texture meter, and x-ray computed tomography (CT) scanning. A dynamic friction tester was also used to measure the friction resistance of the same surfaces. Asphalt and Portland cement concrete samples of various mix designs and finishes and other commonly manufactured textured samples were used. Relationship between the macrotexture and friction was investigated. Mean texture depth (MTD) of 26 laboratory specimens was obtained from volumetric sand patch tests. Two-dimensional profiles and mean profile depth (MPD) of specimens were measured by a laser profiler. A laser texture scanner and a circular texture meter were also used to calculate the MPD of sample surfaces. Three-dimensional rendering of the surfaces were obtained from laser texture scanner and x-ray CT scans. Using the experimental data collected in this study, relationships between friction resistance and macrotexture obtained from different methods were investigated. The estimated texture depths predicted from laser profiler, laser texture scanner, and CT meter were comparable to the MTD obtained from sand patch tests. Also, the friction resistance increased with increasing surface macrotexture.